Experimental Investigation on Temperature Field of a Double-Row Tapered Roller Bearing. Issue 6 (2nd November 2019) - Zhou, Xianwen; Zhu, Qingyu; Wen, Baogang; Zhao, Guang; Han, Qingkai
Abstract: Based on the structural features of a double-row tapered roller bearing (DTRB), a test rig for multipoint temperature measurement was built to investigate the temperature filed characteristics of DTRB under different operating conditions. Firstly, the composition of the test rig and the measuring instruments are described and the loading method is introduced. Secondly, a multipoint temperature measurement method for inner and outer rings of DTRBs is introduced, including the arrangement of the sensors and the signal transmission. Finally, the influence of rotational speed and external load on the circumferential, axial, and radial temperature rise and temperature distribution in a DTRB is studied. Results show that for the stationary bearing outer ring, the temperature rise in the load zone is significantly higher than that in the non-load zone. Under combined load, there are obvious temperature differences in the axial, circumferential, and radial directions of a DTRB.